Manajemen Pengembangan Profesionalisme Guru dalam Meningkatkan Kompetensi Pedagogik di Madrasah: Management of Teacher Professionalism Development in Improving Pedagogic Competence in Madrasah - Hindanah Hindanah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2015)
The development of human resource quality, especially teachers, is a necessity for Islamic educational institutions, as teachers in schools are one of the key components and the main factor in the success of the teaching and learning process. School quality, particularly the quality of students, is often associated with the quality of its teachers, given that teachers are directly involved and interact with students in the classroom. Pedagogic competence refers to the ability to manage student learning, which includes understanding students, designing and implementing learning, evaluating learning outcomes, and developing students to actualize their potential. Pengembangan mutu sumber daya manusia, khususnya guru, merupakan keharusan bagi lembaga pendidikan Islam, karena guru di institusi sekolah adalah salah satu komponen penting dan kunci utama keberhasilan proses belajar mengajar di sekolah. Mutu sekolah, khususnya mutu anak didik, sering dikaitkan dengan mutu guru-gurunya, mengingat guru adalah orang yang langsung terlibat dan berhadapan dengan anak didik di kelas. Kompetensi pedagogik merupakan kemampuan mengelola pembelajaran peserta didik yang meliputi pemahaman terhadap peserta didik, perancangan dan pelaksanaan pembelajaran, evaluasi hasil belajar, dan pengembangan peserta didik untuk mengaktualisasikan berbagai potensi yang dimilikinya.